1999
DOI: 10.1002/(sici)1097-0061(199910)15:14<1449::aid-yea469>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Role of the sulphate assimilation pathway in utilization of glutathione as a sulphur source bySaccharomyces cerevisiae

Abstract: Mutants unable to grow on medium containing glutathione as a sole source of sulphur (GSH medium) were isolated from Saccharomyces cerevisiae strains carrying met17(deficiency of O‐acetylserine and O‐acetylhomoserine sulphydrylase). They were defective in the high‐affinity glutathione transport system, GSH‐P1. Newly acquired mutations belonged to the same complementation group, gsh11. However, it became apparent that gsh11 conferred the mutant phenotype not by itself but in collaboration with met17. Moreover, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This previous study showed that starvation for sulfur resulted in a depletion of the cellular GSH pool, largely through the action of ␥-glutamyl transpeptidase. A more recent report also highlighted the role of GSH as a source of sulfur and suggested a direct link between GSH depletion and SO 4 accumulation in yeast (37). It seems reasonable to suppose that in response to GSH depletion through starvation for sulfur, cellular GSH levels will eventually need to be replenished.…”
Section: Discussionmentioning
confidence: 99%
“…This previous study showed that starvation for sulfur resulted in a depletion of the cellular GSH pool, largely through the action of ␥-glutamyl transpeptidase. A more recent report also highlighted the role of GSH as a source of sulfur and suggested a direct link between GSH depletion and SO 4 accumulation in yeast (37). It seems reasonable to suppose that in response to GSH depletion through starvation for sulfur, cellular GSH levels will eventually need to be replenished.…”
Section: Discussionmentioning
confidence: 99%
“…We observed enrichment of the cytoplasmic protein O-acetylhomoserine sulfhydrolase (MET17, Fig. 2B, panel 5), a protein central for sulfur metabolism and glutathione synthesis (37). Glutathione is a known antioxidant in yeast (13,38).…”
Section: Identified Proteins Differentially Found In Mitochondrial Exmentioning
confidence: 99%
“…Under conditions of sulfur starvation, glutathione is the last of various sulfur-containing compounds to decrease in the cell. 1 It is also known that, under conditions of sulfur starvation, Saccharomyces cerevisiae utilizes sulfate, produced by the consumption of glutathione, as a sulfur source (16). Therefore, it appears that maintenance of the intracellular level of glutathione is of great importance for viability in terms of sustaining sulfur metabolism and protecting the cell from oxidative stress.…”
mentioning
confidence: 99%